Anemia, weight, and height among children under five in Peru (2007-2022): a panel data analysis - Arizmendi, Luis Felipe; de la Torre Domingo, Carlos; Rengifo, Erick W. (My University, 2025)
Panel data methods are becoming crucial in econometrics and social sciences for analyzing data that follows the same entities (such as individuals, firms, countries) over multiple time periods. In this article, we employ a useful approach (Feasible Generalized Least Squares) to assess if there are statistically relevant relationships between hemoglobin (adjusted to sea-level), weight, and height for the period 2007¿2022 in children up to five years of age in Peru. By using this method, we may find a tool that allow us to confirm if the relationships considered between the target variables by the Peruvian agencies and authorities are in the right direction to fight against chronic malnutrition and stunting.While health policies aimed at reducing anemia and improving nutrition, such as supplementation programs and maternal education initiatives, may have contributed to these trends, further research with multidisciplinary collaboration is necessary to quantify the specific impact of these interventions on the observed outcomes.Keywords:Anemia. Children. Anthropometrics. Hemoglobin. Panel Data
Keywords: Anemia. Children. Anthropometrics. Hemoglobin. Panel Data